Applied Linguistics: Analysis of The Translation Methods Used in Translating Poetry "Peace” (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The objective of this research was to describe the ability of the fourth semester students in translating a poetry entitled Peace from English to Indonesian. The research is to find the translation method that used by the students in translating poetry and to identify the most dominant translation method that used by the students in translating a poetry. The subject of the research is the fourth semester students of English Department in Universitas HKBP Nommensen Pematangsiantar (UHKBPNP). The data was a translation test. The research used descriptive qualitative method as a research design. Result of the research shows there are 6 types of translation method that used by the students in translating the poetry, they are word-for-word translation (1,75 %), literal translation (20,27%), faithful translation (25,66%), free translation (30,03%), communicative translation (12,93%), semantic translation (10,16%), since the other method are rarely to use for translating poetry. And the most dominant translation method that used by the students is free translation (30,03%).